The Effect of Physical Training Program for Fitness Improvement on Sickness Absence of Workers at a Chemical Company in Indonesia - Johan, Anita; Kekalih, Aria; Purwito Adi, Nuri; W. Roestam, Ambar; S. Soemarko, Dewi (UI Scholars Hub, 2023)
Introduction. Sickness absence, which can be caused by an unhealthy lifestyle, is an important productivity parameter for the company. Therefore, there are many wellness programs developed in the workplace in an effort to improve workers’ health, fitness, and productivity. The aim of this study was to assess the effect of a physical training program for fitness improvement (VO2 max value) on sickness absence. Methods. This study was conducted by observing the results of the workers' physical training program in the chemical company during 2018, using a cohort retrospective design. SPSS Statistics version 22.0 was used for analysis, with the chi-square test for bivariate analysis and logistic regression for multivariate analysis. Results. The analysis showed that there was a significant difference between the active group (AG) and inactive group (IG) in improving fitness (adjusted RR 4.82, CI 95% 1.54-15.05) and decreasing sickness absence (adjusted RR 3.46, CI 95% 1.03- 11.57). In addition, it was found that participants with normal weight were more likely to increase fitness compared to participants with overweight or obesity (adjusted RR 3.57, 95% CI 1.09-11.64). Conclusion. Participating in a physical training program has been shown to improve fitness levels and reduce sickness absence. Normal nutritional status is more likely to have improved fitness than overweight or obese.